Exploring Students' Difficulties in TOEFL Listening - La'biran, Roni; Dewi, Resnita (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Â The purpose of this study was to determine the difficulties that students face when listening to TOEFL Preparation Tests at the English Study Program, FKIP UKI TORAJA. The participants in this study consisted of 12 students from the 8th semester of the English Department at FKIP UKI Toraja. The research employed a descriptive qualitative method and collected data through interviews. The data was then analyzed using three main stages: data reduction, data display, and drawing conclusions. After analyzing and discussing the findings, it can be concluded that 8th semester English Department students at UKI Toraja encounter various difficulties when listening to TOEFL Preparation tests, which can be categorized into three main areas. Each category presents different challenges. Regarding the comprehension of listening materials, students face difficulties with complex grammatical structures, understanding every word in spoken discourse, interpreting the meaning of lengthy spoken texts, and encountering unfamiliar vocabulary. Additionally, students encounter difficulties related to listening itself, including anxiety, deducing the meaning of unknown words, lack of concentration, unclear pronunciation, difficulty with retention, losing focus, and listening without transcripts. Furthermore, students also face obstacles related to the physical setting, such as poor quality cassettes or discs, inadequate equipment, and background noise.